A Dublin student doctor [large type] - Taylor, Patrick, 1941- (Taylor, Patrick, 1941- Irish country novel., 2012)
In the 1930s, fresh from a stint in the Royal Navy Reserve and against his father's wishes, Fingal O'Reilly goes to Dublin to study medicine. Facing the arduous demands of Trinity College and Sir Patrick Dun's Hospital, Fingal still manages to box and play rugby - and romance a fetching nurse named Kitty O'Hallorhan. But Dublin is a city of slums, tenements, and brutal poverty. Can Fingal harden himself to the suffering all around him? (Bestseller)